Perseverance according to the Book of Job 2:1-13 and implications for people today - Ferry S.N. Lumintang (International Journal Labs, 2024)
Human understanding today is always presented with the concept that those who obey and are faithful to God will be blessed and those who do evil will suffer. On the other hand, humans always want to have something obtained instantly. The book of Job struggles with that understanding and attempts to decipher the concept of recompense. Because of the reality of life in this world, humans are always faced with two sides of life, namely difficult and happy. Researchers use qualitative methods with a literature approach (librabry Research) for this paper. Job's struggles, as the book of Job testifies, are evidence of his perseverance in facing everything in life. Contrary to the concept in Israel that obedience and faithfulness bring blessings. The concept of Job in the face of hardship and pleasure is a character that every human or believer must possess. It turns out that the concept of God as the giver of blessings and punishments based on human works was renewed into a God far beyond human thought and wisdom. Man has limitations to experience God's work in this world. Man's tendency to frame God in man's limited thinking makes it difficult for man to understand what God has done. Olh is therefore in chapters 2:1-13 (are we willing to receive good from God, but not bad? Here comes Job's perseverance.)